Structural and optical characteristics determined by the sputtering deposition conditions of oxide thin films - Prepelita, Petronela; Garoi, Florin; Craciun, Valentin (Beilstein Journal of Nanotechnology, 2021)
The influence of film thickness on the structural and optical properties of silicon dioxide (SiO2) and zinc oxide (ZnO) thin films deposited by radio frequency magnetron sputtering on quartz substrates was investigated. The deposition conditions were optimized to achieve stoichiometric thin films. The orientation of crystallites, structure, and composition were investigated by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), while the surface topography of the samples was analyzed using scanning electron microscopy (SEM). The optical characteristics were measured for samples with the same composition but obtained with different deposition parameters, such as increasing thickness. The optical constants (i.e., the refractive index n, the extinction coefficient k, and the absorption coefficient α) of the SiO2 and ZnO oxide films were determined from the transmission spectra recorded in the range of 190–2500 nm by using the Swanepoel method, while the energy bandgap was calculated from the absorption spectra. The influence of thickness on the structural and optical properties of the oxide films was investigated. Good optical quality and performance were noticed, which makes these thin films worthy of integration into metamaterial structures.
Keywords: magnetron sputtering; optical quality; SiO2 and ZnO; structural properties; thin films

(untitled) - Zeng, X.; Pelenovich, V.; Xing, B.; Rakhimov, R.; Zuo, W.; Tolstogouzov, A.; Liu, C.; Fu, D.; Xiao, X. (Beilstein J. Nanotechnol., 2020)

(untitled) - Blumenstein, N. J.; Streb, F.; Walheim, S.; Schimmel, T.; Burghard, Z.; Bill, J. (Beilstein J. Nanotechnol., 2017)

(untitled) - Tkachenko, V.; Marino, A.; Otón, E.; Bennis, N.; Otón, J. M. (Beilstein J. Nanotechnol., 2016)

(untitled) - Ashrafi, A.; Jagadish, C. (J. Appl. Phys., 2020)

(untitled) - Zhu, X.; Jhang, J.-H.; Zhou, C.; Dagdeviren, O. E.; Chen, Z.; Schwarz, U. D.; Altman, E. I. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Alver, Ü.; Tascıoğlu, M. E.; Güler, O.; Aslan, M.; Yazgan, A.; Kaya, H.; Duran, C.; Çuvalcı, H.; Bilgin, S. (J. Inorg. Organomet. Polym. Mater., 2019)

(untitled) - Vural, S.; Köytepe, S.; Seçkin, T.; Adıgüzel, İ. (Polym.-Plast. Technol. Eng., 2012)

(untitled) - Chang, L.-M.; Hou, Y.-D.; Zhu, M.-K.; Yan, H. (J. Appl. Phys., 2007)

(untitled) - Paldi, R. L.; Wang, X.; Sun, X.; He, Z.; Qi, Z.; Zhang, X.; Wang, H. (Nano Lett., 2020)

(untitled) - Rogov, A.; Narimanov, E. (ACS Photonics, 2018)

(untitled) - Karpov, E. G.; Danso, L. A.; Klein, J. T. (Phys. Rev. E, 2017)

(untitled) - Singh, P.; Thapa, K. B.; Kumar, N.; Singh, D.; Kumar, D. (Results Phys., 2019)

(untitled) - Tsai, C.-Y.; Lai, J.-D.; Feng, S.-W.; Huang, C.-J.; Chen, C.-H.; Yang, F.-W.; Wang, H.-C.; Tu, L.-W. (Beilstein J. Nanotechnol., 2017)

(untitled) - Saadaoui, S.; Ben Youssef, M. A.; Ben Karoui, M.; Gharbi, R.; Smecca, E.; Strano, V.; Mirabella, S.; Alberti, A.; Puglisi, R. A. (Beilstein J. Nanotechnol., 2017)

(untitled) - Das, A. (Curr. Sci., 2019)

(untitled) - Danewalia, S. S.; Khan, S.; Dhillon, S.; Bansal, N.; Sharma, G.; Singh, K. (Ionics, 2020)

(untitled) - Xu, X.; Prüfer, T.; Wolf, D.; Engelmann, H.-J.; Bischoff, L.; Hübner, R.; Heinig, K.-H.; Möller, W.; Facsko, S.; von Borany, J.; Hlawacek, G. (Beilstein J. Nanotechnol., 2018)

(untitled) - Alipour, A.; Farmani, A.; Mir, A. (Plasmonics, 2020)

(untitled) - Polydorou, E.; Soultati, A.; Vasilopoulou, M. (J. Mater. Chem. C, 2016)

(untitled) - Marcu, A.; Viespe, C. (Sens. Actuators, B, 2015)

(untitled) - Zhang, H.-D.; Liu, Y.-J.; Zhang, J.; Zhu, J.-W.; Qin, Q.-H.; Zhao, C.-Z.; Li, X.; Zhang, J.-C.; Long, Y.-Z. (J. Phys. D: Appl. Phys., 2018)

(untitled) - Jia, C.; Ren, Y.; Yin, Y.; Zhang, W. (Appl. Phys. Lett., 2019)

(untitled) - Schössler, T.; Schön, F.; Lemier, C.; Urban, G. (Thin Solid Films, 2020)

(untitled) - Socol, M.; Preda, N.; Costas, A.; Borca, B.; Popescu-Pelin, G.; Mihailescu, A.; Socol, G.; Stanculescu, A. (Nanomaterials, 2020)

(untitled) - Radu, A. I.; Filipescu, M.; Dumitru, M.; Moldovan, A.; Dinescu, M.; Antohe, S. (Rom. Rep. Phys., 2020)

(untitled) - Stoleriu, S.; Lungu, C.; Ghitulica, C. D.; Surdu, A.; Voicu, G.; Cucuruz, A.; Turculet, C. S.; Ciocan, L. T. (Nanomaterials, 2020)

(untitled) - Kim, Y. H.; Shin, D. W.; Kim, J. S.; Song, J.-H.; Yoon, S.-J.; Park, K. B.; Choi, J.-W. (Ceram. Int., 2012)

(untitled) - Stavarache, I. (Dig. J. Nanomater. Biostructures, 2011)

(untitled) - Rahmane, S.; Djouadi, M. A. (J. Mater. Sci.: Mater. Electron., 2020)

(untitled) - Sultan, M. T.; Maraloiu, A. V.; Stavarache, I.; Gudmundsson, J. T.; Manolescu, A.; Teodorescu, V. S.; Ciurea, M. L.; Svavarsson, H. G. (Beilstein J. Nanotechnol., 2019)

(untitled) - Rad, Z. S. J.; Afzalzadeh, R. (Sci. Iran., Trans. F, 2017)

(untitled) - Prepelita, P.; Baban, C.; Iacomi, F. (J. Optoelectron. Adv. Mater., 2007)

(untitled) - Rambu, A. P.; Iftimie, N. (Bull. Mater. Sci., 2014)

(untitled) - Bai, Y.; Li, Y.; Wang, J.; Fan, W.; Li, Z.; Fu, Y.; Lu, Y.; Wang, W. (Integr. Ferroelectr., 2020)

(untitled) - Schumann, E.; Hübner, R.; Grenzer, J.; Gemming, S.; Krause, M. (Nanomaterials, 2018)

(untitled) - Prepelita, P.; Stefan, N.; Luculescu, C.; Garoi, F.; Birjega, R. (Thin Solid Films, 2012)

(untitled) - Stavarache, I.; Ciurea, M. L. (J. Optoelectron. Adv. Mater., 2007)

Elements of X-Ray Diffraction - Cullity, B. D. (Addison-Wesley, 1978)

Physical Methods for Materials Characterisation - Flewitt, P. E. J.; Wild, R. K. (IOP Publishing LTD, 1994)

Structure of Metals - Barret, C. S.; Massalski, T. B. (Pergamon Press, 1980)

(untitled) - Moholkar, A. V.; Pawar, S. M.; Rajpure, K. Y.; Patil, P. S.; Bhosale, C. H. (J. Phys. Chem. Solids, 2007)

(untitled) - Görlich, E.; Haber, J.; Stoch, A.; Stoch, J. (J. Solid State Chem., 1980)
Element Si, 2p3/2, Formula SiO2, CAS Registry No 60676-86-0, Binding Energy 103.7 eV.

(untitled) - Miller, M. L.; Linton, R. W. (Anal. Chem. (Washington, DC, U. S.), 1985)
Element O, 1s2, Formula SiO2, CAS Registry No 60676-86-0, Binding Energy 532.5 eV.

(untitled) - Donley, M. S.; Baer, D. R.; Stoebe, T. G. (Surf. Interface Anal., 1988)
Element Si, 2p3/2, Formula SiO2, CAS Registry No 60676-86-0, Binding Energy 103.3 eV.

(untitled) - Kovacich, J. A.; Lichtman, D. (J. Electron Spectrosc. Relat. Phenom., 1985)
Element O, 1s2, Formula SiO2, CAS Registry No 60676-86-0, Binding Energy 532.4 eV.

(untitled) - Prepelita, P.; Stavarache, I.; Craciun, D.; Garoi, F.; Negrila, C.; Sbarcea, B. G.; Craciun, V. (Beilstein J. Nanotechnol., 2019)

(untitled) - Popa, C.; Bratu, A. M.; Bacalum, M.; Prepelita, P. (Sustainable Chem. Pharm., 2020)

(untitled) - Barr, T. L.; Yin, M.; Varma, S. (J. Vac. Sci. Technol., A, 1992)
Element Zn, 2p2/3, Formula ZnO, CAS Registry No 1314-13-2, Binding Energy 1022.1 eV.

(untitled) - Battistoni, C.; Dormann, J. L.; Fiorani, D.; Paparazzo, E.; Viticoli, S. (Solid State Commun., 1981)
Element O, 1s2, Formula ZnO, CAS Registry No 1314–13-2, Binding Energy 531.2 eV.

(untitled) - Stavarache, I.; Logofatu, C.; Sultan, M. T.; Manolescu, A.; Svavarsson, H. G.; Teodorescu, V. S.; Ciurea, M. L. (Sci. Rep., 2020)

(untitled) - Swanepoel, R. (J. Phys. E: Sci. Instrum., 1983)

(untitled) - Prepelita, P.; Craciun, V.; Sbarcea, G.; Garoi, F. (Appl. Surf. Sci., 2014)

Properties of Wide Bandgap II–VI Semiconductors - Bangava, R. (EMIS Inspect, 1997)

Optical Absorbtion and Dispersion in Solids - Hodgson, J. N. (Chapman & Hall, 1970)

Zinc Oxide Bulk, Thin Films and Nanostructures; Processing, Properties and Applications - Jagadish, C.; Pearson, S. J. (Elsevier, 2006)

(untitled) - Alsaad, A. M.; Al-Bataineh, Q. M.; Ahmad, A. A.; Albataineh, Z.; Telfah, A. (Optik (Munich, Ger.), 2020)

(untitled) - Zhao, J. L.; Sun, X. W.; Ryu, H.; Moon, Y. B. (Opt. Mater., 2011)

(untitled) - Naik, G. V.; Shalaev, V. M.; Boltasseva, A. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Sinol, M.; Rani, E. (J. Neutrino, 2017)

(untitled) - Gric, T.; Hess, O. (J. Appl. Phys., 2017)

(untitled) - Salary, M. M.; Mosallaei, H. (Sci. Rep., 2017)

(untitled) - Alisafaee, H.; Cox, P. M.; Fiddy, M. A. (Proc. SPIE, 2013)